2022
DOI: 10.1111/pce.14490
|View full text |Cite
|
Sign up to set email alerts
|

Local diversity of drought resistance and resilience in Populus tomentosa correlates with the variation of DNA methylation

Abstract: Little information is known about DNA methylation variation in shaping environment-specific drought resistance and resilience for tree adaptation. In this study, we leveraged RNA sequencing and whole-genome bisulfite sequencing data to dissect the distinction of epigenetic regulation under drought stress and rewater condition of Populus tomentosa accessions from three geographical regions. We demonstrated low resistance and high resilience for accessions from South. Non-CG methylation levels in promoter region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 108 publications
0
8
0
Order By: Relevance
“…uralensis. Previous studies revealed that genes related to osmotic and antioxidant regulation rapidly respond to water stress, , and these pathways were also enriched and highlighted in our results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…uralensis. Previous studies revealed that genes related to osmotic and antioxidant regulation rapidly respond to water stress, , and these pathways were also enriched and highlighted in our results.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, DMGs were also enriched in phenylpropanoid and flavonoid biosynthesis pathways (Figure 5), which suggested that drought stress and rewatering changed the methylation status of genes involved in the synthesis of secondary metabolites in G. uralensis. Previous studies revealed that genes related to osmotic and antioxidant regulation rapidly respond to water stress, 31,38 and these pathways were also enriched and highlighted in our results. Differential Metabolite Analysis.…”
Section: Correlation Between Dna Methylation Status and Gene Expressi...mentioning
confidence: 99%
“…The complex interplay between genotype and environment combined with the limited number of biological replicates, resulted in limited power of this study to identify causal epigenetic variants. However, Zhou et al [ 45 ] detected a functional relationship between DNA-methylation diversity and drought resistance and resilience in Populus tomentosa by combining epigenome-wide association studies with genome-wide association studies. Further research is needed building on our findings to help understand the mechanisms by which DNA methylation epialleles are generated, maintained and erased, and their functional consequences in plants.…”
Section: Discussionmentioning
confidence: 99%
“…The complex interplay between genotype and environment combined with the limited number of biological replicates, resulted in limited power of this study to identify causal epigenetic variants. However, Zhou et al [42] detected a functional relationship between DNA-methylation diversity and drought resistance and resilience in Populus tomentosa by combining epigenome-wide association studies with genome-wide association studies. Further research is needed building on our findings to help understand the mechanisms by which DNA methylation epialleles are generated, maintained and erased, and their functional consequences in plants.…”
Section: Discussionmentioning
confidence: 99%